2018
DOI: 10.1007/s40279-018-0914-4
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Resistance Training in Female Youth: Its Effect on Muscular Strength, and Shortcomings in the Literature

Abstract: Resistance training is effective in female youth. These findings can be used to inform the prescription of RT in female youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 85 publications
3
76
6
Order By: Relevance
“…That we observed better reliability in those pre‐PHV than their more mature counterparts might be due to the well‐established disruptions in motor performance that occur during maturation . Moreover, these data reinforce the importance of categorizing youths by maturation rather than chronological age y . Nonetheless, the reliability of left and right limb, bilateral and relative peak force for the mid‐post‐PHV group was still acceptable and thus typical changes in strength can still be detected.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…That we observed better reliability in those pre‐PHV than their more mature counterparts might be due to the well‐established disruptions in motor performance that occur during maturation . Moreover, these data reinforce the importance of categorizing youths by maturation rather than chronological age y . Nonetheless, the reliability of left and right limb, bilateral and relative peak force for the mid‐post‐PHV group was still acceptable and thus typical changes in strength can still be detected.…”
Section: Discussionsupporting
confidence: 66%
“…34 Moreover, these data reinforce the importance of categorizing youths by maturation rather than chronological age y. 11,41 Nonetheless, the reliability of left and right limb, bilateral and relative peak force for the midpost-PHV group was still acceptable and thus typical changes in strength can still be detected.…”
Section: Discussionmentioning
confidence: 75%
“…Such results seems to contrast with those observed after traditional resistance training programs in youths. For example, a recent meta-analysis (28) observed greater gains in maximal strength in older more mature females (ES=0.72) compared to their younger less mature counterparts (ES=0.38) when resistance training interventions were analyzed. Similarly, in a study conducted in male youth (31), greater gains in maximal strength were observed in older more mature youth (ES=1.3, large) compared to their younger less mature counterparts (ES=0.8, moderate) after 8 weeks of resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…However, to optimize strength enhancement, it seems that the combination of different types of plyometrics with weight-training is a relevant issue (49). Considering that maturation may exert a moderating role in the adaptive response of maximal strength of youth after resistance training (28,31), further research is warranted in regard to the potential role of maturation on the adaptive response of maximal strength of youth after combined resistance training and different doses of plyometric jump drills.…”
Section: Discussionmentioning
confidence: 99%
“…It is note worthy that the female players in our study did not show any differences in shoulder strength during their three-year period at a handball-profiled secondary school. It is doubtful that growth maturity per se would be a significant primary factor here, since several previous studies have shown that other strength and power measures such as bench press, counter movement jumps, deep squat and clean jerks could be improved significantly during this age period in female players (124,125). The lack of increased shoulder strength in females during this period is a novel and interesting finding that could contribute to the higher prevalence of shoulder problems seen in the female players in this thesis.…”
Section: School Grade Differences In Shoulder Strengthmentioning
confidence: 98%